The effect of nitrogen on the growth and development of giant witchweed, Striga hermonthica Benth: effect on cultured germinated seedlings in host absence - Igbinnosa, I.; Cardwell, K.F.; Okonkwo, S.N.C. (Springer, 1996)
For the first time in sterile nutrient media in the absence of the host plant, different forms and rates of nitrogen compounds were screened for their effect on S. hermonthica Benth. shoot development beyond seed germination. There was no shoot formation beyond the inoculation stages when S. hermonthica germlings were grown in media devoid of nitrogen source. In culture media containing some nitrogen sources, healthy shoots were formed. Increasing concentrations ofKN03, NaN03, Ca(N03h, Mg(N03h and asparagine resulted in a significant increase in S. hermonthica shoot development. Inversely, increasing concentrations of (NH4hS04, NH4H2P04, NH4CI and urea led to increasing significant reduction of S. hermonthica shoot development. The amino acids, glycine and asparagine supported reduced shoot development of S. hermonthica, indicating that organic nitrogen cannot replace inorganic nitrogen for Striga growth. The ammonium nitrogen compounds, (NH4hS04 and NH4H2P04, suppressed further shoot elongation and total dry weight of 20 and 40 days old Striga hermonthica plants, in sterile culture media. The organic compounds urea, allylthiourea and thiourea had an effect similar to ammonium compounds. Arginine and glycine on the other hand did not suppress the further development of the parasite. The suppressive effect of nitrogen however, was greater when the parasite was 20 days old than when it was 40 days old. This work provides data to show that some nitrogen compounds reduce the severity of S. hermonthica attack by direct suppression of Striga growth and development at the post-germination stage and after shoots have been formed.